Developing an Integrated Evaluation Model for Physician Comprehensive Workload Tethered to Outpatient Practice: An Empirical Study From China - Li, Dehe; Hu, Yinhuan; Liu, Sha; Lu, Chuntao; Zhang, Yeyan; Zhou, Jinghan; Li, Jiayi; Zhang, Zemiao (Frontiers in Public Health, 2022)
Background: Previous studies, often simply using either objective workload or mental workload as a measure of physician workload in various healthcare settings might have failed to comprehensively reflect the real workload among physicians. Despite this, there is little research that further explores a comprehensive workload evaluation framework with the integration of objective workload and mental workload to describe their comprehensive workload. Methods: A comprehensive evaluation framework for physician workload was proposed based on the combination of objective workload and task-level mental workload also with the consideration of quality of provided medical services and served patient complexity; and accordingly, an integrated evaluation model for physician comprehensive workload (PCW) tethered to outpatient practice was developed and further applied to perform a PCW analysis using cross-sectional data on outpatient workload of 1934 physicians mainly from 24 hospitals in 6 provinces in Eastern, Central, and Western China. Multiple linear regression and multinomial logistic regression analyses were established to identify significant factors influencing the PCW. Results: Overall, the average score of PCW tethered to outpatient practice Chinese physicians experienced was 811.30 (SD=494.98) with concentrating on between 200 and 1200. Physicians who were female, from Eastern or Western China, and those who worked >60 hours per week and longer outpatient hours per week were more likely to experience a higher PCW. 11.2% of participating physicians were identified as very high PCW physicians, compared with 11.6% as low PCW physicians, 45.5% as medium PCW physicians and 30.7% as high PCW physicians. Those who were female, older, from Western China, those who had lower educational levels, lower professional titles and longer working years in the current institution, and those who worked in tertiary A hospitals and Internal or Surgical, and worked >60 hours per week and longer outpatient hours per week were more likely to be very high PCW physicians. Conclusions: Our work has a potential application for comprehensively assessing physician workload tethered to outpatient practice and could provide a solid foundation for hospital managers to further accurately determine and identify physicians with high workload, who would otherwise be missed in either objective workload or mental workload.